Early Childhood Administrators Views on LGBTQ Books: A Mixed Methods Study - Archana V. Hegde; Paige Averett; Madison Alexander; Lanie P. Holmes; Anne Ticknor (Education Sciences, 2025)
There is limited empirical literature on the study of LGBTQ books, and even less on the perspective of early childhood center administrators on these books. Hence, a mixed methods study surveying the administrators of high-quality early childhood centers across the state of North Carolina was implemented. Sixty-five participants completed the survey, and both quantitative and qualitative data were gathered and analyzed. The findings indicated that the majority (64%) of the administrators had read at least one book from the listed LGBTQ books, while the rest had never read a single book from the listing. Their familiarity with the book content was based on reading the book only once, and they only “somewhat” recalled the content of the book. These findings indicate a lack of regular use of LGBTQ books in the centers. The administrators made both negative and positive comments on the survey administered and the books in general. The results indicate a need for education and training to focus on the connection of LGBTQ topics and how they are developmentally appropriate, as well as the connection to the NAEYC Code of Ethics.